Identification of Unique Genetic Sources of Soybean Rust Resistance from the USDA Soybean Germplasm Collection. Issue 5 (1st September 2015) - Harris, Donna K.; Kendrick, Mandy D.; King, Zachary R.; Pedley, Kerry F.; Walker, David R.; Cregan, Perry B.; Buck, James W.; Phillips, Daniel V.; Li, Zenglu; Boerma, H. Roger
ABSTRACT: Soybean [ Glycine max (L.) Merr.] rust is caused by the fungal pathogen Phakopsora pachyrhizi . Six rust resistance loci ( Rpp1, 2, 3, 4, 5, and 6 ) have been reported. Crosses were made between 75 resistant plant introductions (PIs) and a susceptible elite line or cultivar. Bulked segregant analysis (BSA) was used to determine if the PI resistance genes mapped to a previously identified locus or to an unreported locus. Fifty‐two PIs had resistance genes that mapped to the Rpp3 region on chromosome 6 of the soybean genome. A set of P. pachyrhizi isolates was used to further characterize the resistance of these PIs. Forty‐two of the PIs exhibited the same reaction profiles as either PI 462312 ( Rpp3 ) or 'Hyuuga' ( Rpp3 and Rpp5 ) to the panel of isolates. The fine mapping of Rpp1, Rpp3, and Rpp4 and the availability of the SoySNP50K Infinium Chip data on the USDA Soybean Germplasm Collection made it possible to use BSA and isolate data on these PIs to determine in retrospect how effective haplotype analysis would be in narrowing down the PIs to those likely to have a unique source of resistance. Thirty‐seven of the 52 PIs (71%) mapping to the Rpp3 region had a haplotype identical to that of PI 462312. A combination of these analyses could prove useful in more rapidly narrowing down resistant PIs to those likely to carry a unique resistance gene.